It Takes “Guts” to Cause Joint Inflammation: Role of Innate-Like T Cells - Mortier, Céline; Govindarajan, Srinath; Venken, Koen; Elewaut, Dirk (Frontiers in Immunology, 2018)
Innate-like T cells such as invariant natural killer T (iNKT) cells and mucosal-associated T (MAIT) cells, characterized by a semi-invariant T cell receptor and restriction toward MHC-like molecules (CD1 and MR1 respectively), are a unique unconventional immune subset acting at the interface of innate and adaptive immunity. Highly represented at barrier sites and capable of rapidly producing substantial amounts of cytokines, they serve a pivotal role as first-line responders against microbial infections. In contrast, it was demonstrated that innate-like T cells can be skewed toward a predominant pro-inflammatory state and are consequently involved in a number of autoimmune and inflammatory diseases like inflammatory bowel diseases and rheumatic disorders, such as spondyloarthritis (SpA) and rheumatoid arthritis. Interestingly, there is link between gut and joint disease as they often co-incide and share certain aspects of the pathogenesis such as established genetic risk factors, a critical role for pro-inflammatory cytokines, such as TNF-α, IL-23, and IL-17 and therapeutic susceptibility. In this regard dysregulated IL-23/IL-17 responses appear to be crucial in both debilitating pathologies and innate-like T cells likely act as key player. In this review, we will explore the remarkable features of iNKT cells and MAIT cells, and discuss their contribution to immunity and combined gut–joint disease.